2015
DOI: 10.1097/qai.0000000000000421
|View full text |Cite
|
Sign up to set email alerts
|

HIV Test Offers and Acceptance

Abstract: We found evidence of partial and increasing implementation of the HIV testing law. Importantly, these studies demonstrated New Yorkers' willingness to accept an offered HIV test as part of routine care in health care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Specific demographic groups had disparate HIV screening rates in the past year in our deaf sample, with increased rates of recent HIV screening found among younger adults (18-34), nonCaucasian adults, and persons who identified as LGBQ. These results from our study were like other studies that identified MSM, Black, and younger adults as more likely to have received screening [9-12]. This suggests that hearing status or language use did not change the pattern of other sociodemographic factors contributing to HIV screening uptake likelihood.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Specific demographic groups had disparate HIV screening rates in the past year in our deaf sample, with increased rates of recent HIV screening found among younger adults (18-34), nonCaucasian adults, and persons who identified as LGBQ. These results from our study were like other studies that identified MSM, Black, and younger adults as more likely to have received screening [9-12]. This suggests that hearing status or language use did not change the pattern of other sociodemographic factors contributing to HIV screening uptake likelihood.…”
Section: Discussionsupporting
confidence: 87%
“…Prior research has explored demographic characteristics associated with HIV screening uptake [9-13], as well as the potential of using the internet and social networking sites as outreach avenues to increase HIV screening, particularly among high risk groups [16,19,22,33,34]. Our study expands such research to US-based deaf adults who use ASL, estimates the prevalence of HIV screening uptake in this medically underserved group, and investigates the role of social media as a predictor of HIV screening uptake among deaf adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data regarding the implementation of the New York testing law suggest that the frequency of HIV testing is improving [ 15–19 ]. Survey data from 2011 to 2012 showed that only 25% of New York residents aged 18–64 years who had sought medical care in the past year were offered an HIV test at that visit, with 60% of those accepting the offer [ 17 ]. By the end of our study, we found substantial increases in HIV testing.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the USPSTF recommendation, many physicians screen based on risk stratification or by patient request [6][7][8]. Factors found to increase the likelihood that a person receives an HIV test include: being MSM [9,10], a young adult [11], black [10,12], having recent STD testing or an STD diagnosis [13], and having access to HIV screening [13]. Gender has been found to indicate both higher and lower likelihood of receiving HIV screening [9][10][11]13].…”
Section: Introductionmentioning
confidence: 99%